Effects of Superliv Concentrate on the Growth, Immunocompetence Traits and Nutrient Retention of Commercial Broilers During Extreme Winter - Bhattacharyya, Amitav; Garg, Satish Kumar; Kumar, Vinod; Roy, Debashish; Ravikanth, K.; Maini , Shivi (International Journal of Poultry Science, 2012)
A study was conducted during the months of December-January involving sixty one week old broiler chickens, distributed into two experimental groups having three replicates of ten birds each. The birds of the first group were fed a basal diet (22.5% CP & 2830 K cal/kg ME) while the second group birds were fed a basal diet supplemented with a liver tonic, Superliv concentrate (Ayurvet Limited product) @ 50g/quintal. Body weight gain was significantly higher (P